Penatalaksanaan Secara Holistik pada pasien 67 Tahun dengan Ulkus Kaki Diabetikum: Laporan Kasus - Nimas Shifa Azzahra; Aila Karyus (Medula, 2026)
Diabetic foot ulcers are a chronic complication of diabetes mellitus that has a high prevalence globally, including in Indonesia. This condition can lead to a decreased quality of life and increase the risk of infection and amputation. This study discusses the case of a 67-year-old woman with a diabetic foot ulcer who was managed through a comprehensive approach based on EBM to improve the healing process and prevent complications. This study is structured as a case report, with primary data collected through anamnesis, physical examination, and home visits. Secondary data sources were obtained from the patient's medical records at the community health center. The evaluation was conducted using a holistic diagnostic approach, both quantitatively and qualitatively, covering the initial stages, implementation process, and final results of the study. Patient Mrs. H, 67, complained of a wound that had not healed for three months. Additional complaints included frequent hunger, frequent thirst, and frequent urination. In this study, diagnosis and management were carried out in accordance with current guidelines and literature, including glycemic control, wound care, health education, and regular monitoring. After a five-day holistic intervention, there was a decrease in fasting blood glucose from 262 mg/dL to 210 mg/dL (19.8% decrease), improvement in nutritional adequacy figures through food recall obtained data on energy reduction from 60.86% to 33.9%, with details of carbohydrates from 280% to 122.8%, protein 152.9% to 143.2%, and fat from 434% to 325.8% and an increase in patient knowledge scores from 50 to 80 (scale 0-100).